1979
DOI: 10.1128/iai.23.2.305-311.1979
|View full text |Cite
|
Sign up to set email alerts
|

Host defenses in herpes simplex infections of the nervous system: effect of antibody on disease and viral spread

Abstract: BALB/c mice passively immunized with antibody to herpes simplex virus type 1 and challenged in the footpad with 105-7 plaque-forming units of herpes simplex virus type 1 were shown to be protected from neurological disease and death compared with control mice treated with normal serum or antibody to Sindbis virus. One hundred percent of untreated mice had virus recoverable from dorsal root ganglia by 48 h after infection. Whereas amputation of the infected limb at 48 h had no effect, antibody administration (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

1981
1981
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(39 citation statements)
references
References 25 publications
4
35
0
Order By: Relevance
“…This finding no doubt reflects the increased acute clinical illness observed in these animal groups. These results mirror previous studies that have shown that passively administered hyperimmune serum will reduce the number of latently infected ganglia but will not prevent the establishment of latency [McKendall et al, 1979;Openshaw et al, 1979;Price and Schmitz, 19791. It is noteworthy, however, that our findings are somewhat in opposition to results provided by Mc-Kendall [1977], which showed that prior immunization of mice by HSV-1 infection would significantly protect against both acute and latent HSV-2 infection.…”
Section: Discussionsupporting
confidence: 89%
“…This finding no doubt reflects the increased acute clinical illness observed in these animal groups. These results mirror previous studies that have shown that passively administered hyperimmune serum will reduce the number of latently infected ganglia but will not prevent the establishment of latency [McKendall et al, 1979;Openshaw et al, 1979;Price and Schmitz, 19791. It is noteworthy, however, that our findings are somewhat in opposition to results provided by Mc-Kendall [1977], which showed that prior immunization of mice by HSV-1 infection would significantly protect against both acute and latent HSV-2 infection.…”
Section: Discussionsupporting
confidence: 89%
“…Neutralizing antibody can inactivate extracellular viruses but cannot reach the intracellular viruses (12). Thus, cell to cell spreading of HSV within tissues is hardly blocked by the antibody (15,26). This failure of humoral immunity is effectively supplemented by the cell-mediated effector system against HSV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of passively transferred antiviral antibody against primary herpes simplex virus (HSV) infection has been investigated extensively in mouse models (1,6,15,17). Relatively little is known, however, of the mechanisms by which the antibody prevents the spread of infection in vivo.…”
mentioning
confidence: 99%